Three Women, Three Roots, Three Times, One Tree: Some Thoughts for Potential Gardeners - Gunnell, Terry (Religionsvidenskabeligt tidsskrift, 2022)
ABSTRACT: This article considers the potential connections between the three nornir mentioned in Vǫluspá and the three roots of Yggdrasill mentioned in Grímnismál st. 31 and Gylfaginning which, like the nornir themselves, may have been seen (by some) as being connected with time. This raises the possibility that, at some point and for some people, the jǫtnar were closely connected with the world of death and the underworld (which, for some, may have been associated with the east from whence the sun rises). It also raises questions about whether Urðr should be seen as referring to the past, rather than the future, and reconsiders the earlier posited idea that life, death and time were seen as being a circular process much like the natural year.